(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Dental caries is a multifactorial infectious disease that can develop at any age - in early childhood, in adolescence and in adults, throughout life, leading to enamel demineralization with the formation of a carious cavity. According to the WHO, caries remains a significant problem in most of the developed world, affecting 60 to 90% of children and the vast majority of adults. The main method of detecting caries is a thorough visual inspection using a dental probe and mirror. Additional methods include vital staining, radiography, electroodontodiagnostics (EOD), etc. In children in permanent teeth, carious defects are often formed against the background of focal demineralization of teeth. The traditional treatment of caries involves the complete removal of enamel with signs of demineralization. This approach to treatment led to a significant loss of hard tissues and weakening of the supporting structures of the teeth. In a comparative study, the advantages and disadvantages of the studied methods were established and it was found that the most effective is an integrated approach to the clinical situation and a combination of several diagnostic methods, additional use of instrumental diagnostic methods to clarify the diagnosis.